Influence of the international nature of Peruvian companies in sustainability reporting - Hernández Pajares, Julio (2018)
In response to regulations promoted by international institutions and due to the influence of transnational organizations, sustainability reporting has experienced an important development in recent years for Latin American companies. In this line, Peruvian organizations have also participated in reporting initiatives under the model of the Global Reporting Initiative (GRI). For this reason, the aim of this study is to analyze whether the factors of size, transnational nature and international character of its customers are determinants in the level of compliance with the sustainability information of Peruvian companies. This takes as a reference the GRI criteria present in its sustainability reports. Based on this, the results indicate that belonging to transnational groups and relationships with foreign customers do constitute themselves as determining factors in the level of compliance with information on aspects of environmental performance, mainly.